Dilemmas, Challenges and Strategies of Physical Education Teachers-Researchers to Combat Covid-19 (SARS-CoV-2) in Brazil - Silva, Antonio Jansen Fernandes da; Silva, Cybele Câmara da; Tinôco, Rafael de Gois; Araújo, Allyson Carvalho de; Venâncio, Luciana; Sanches Neto, Luiz; Freire, Elisabete dos Santos; Lazaretti da Conceição, Willian (Frontiers in Education, 2021)
This paper addresses the challenges presented by the coronavirus pandemic in Brazil, questioning the strategies and the dilemmas shown by teacher-researchers in Physical Education in tackling Covid-19 (SARS-CoV2). The Covid-19 pandemic has had significant social impacts, such as the sudden interruption of basic education activities in Brazil, due to the need for social isolation. Brazilian basic education comprehends schooling from early childhood education (similarly to kindergarten and preschool in other countries) and elementary school (1st–9th grades) to high school (10th–12th grades). Measures taken as precautions have demanded an overhaul of the teaching systems, pedagogical structures, and strategies for interaction, almost all of these being involved in a teaching process that is mediated by digital technologies. Therefore, one asks just how Physical Education teachers and their respective teaching networks get organized when faced with social isolation, with regard to work strategies for ways to relate to knowledge. The main objective of this article is analysing the pedagogical experiences of teacher-researchers–teachers from state-owned schools and university researchers–in four Brazilian states, namely Ceará, Pará, Rio Grande do Norte and São Paulo, in order to discuss the implications upon Physical Education in schools, as a way to tackle the pandemic through social isolation. This is an exploratory and descriptive study that makes use of narratives. It also includes a project for intervention. The design of this analysis is inspired by the methodological structures of pedagogical cases, which includes narrative accounts, the shared analysis of these accounts by different teachers and researchers, and the synthesis of the analyses in the form of a balance of experiences. There are three dimensions that are integrated into the relationship to knowledge–identitary, social and epistemic dimensions–, that are essential for the Physical Education teachers who narrate the situations they have experienced. Here we consider that the educational process must not be reduced to a mere transmission of information through technological resources and digital platforms. One must also accept and acknowledge that complex teaching situations are inserted in the relationships to knowledge. As such, they must not be regarded as generic and fragmented. The purpose of the intervention project is to collaborate with the practices of Physical Education teachers seeking to prevent, identify, and report on cases of Covid-19 among students and their family members. Social isolation has been the most efficient protective measure to reduce the impact of the spread of the virus, but it comes up against problems to be addressed in Brazil, such as subnotification of cases. In this regard, the project makes a significant contribution toward the fight against the SARS-CoV-2 pandemic. In a certain way, it connects public health actions and the development of communication aids, as well as applications for building of awareness of prevention of health risks, assistance to the most vulnerable and/or isolated people, prevention of the psychological impacts of the health crisis, and the tackling of violence against children during the confinement. Many are, and many shall be, the impacts of Covid-19 upon Brazil and upon the world as a whole. Apart from health and the economy, the pandemic we now face shall have an influence on our system of values and, hence, on our choices and our way of life. This link also becomes explicit when Paulo Freire views education as a political act, with the main intention of stimulating the potential of understanding reality, or in other words “reading the world”, a condition to take part in the organisation of this world. It would not be possible to take social action without taking sides, without making choices; and these choices are firmly anchored to a socially constructed system of values. According to Paulo Freire, this human action should be conscientious. The main role of the educational process should be that of constructing this awareness. Therefore, thinking over the values that guide us is of paramount importance. In current reality, faced with a health problem that interferes with our way of life and in the adoption of a given system of values, education should play a key role for the creation of opportunities to think over values and their reformulations.